Productivity of Annual and Perennial Cool‐Season Grasses Established in Warm‐Season Pasture by No‐till Overseeding or By Conventional Tillage and Sowing. Issue 1 (21st June 2013) - Bartholomew, P. W.
Abstract : In the southern Great Plains (SGP), perennial pasture grasses offer a source of cool‐season forage that does not incur costs and risks associated with production of annual cool‐season forages. However, persistence and lifetime productivity of perennial cool‐season grasses may be compromised by the high temperatures and soil moisture deficits common in the summer months in the SGP. Tall fescue (TF) cultivars Texoma MaxQII (TMQ), Flecha (FLE), and Kentucky 31 (K31) and annual ryegrass cultivar Marshall (IRG) were no‐till overseeded into existing unimproved warm‐season pasture or were sown into a tilled seedbed. Effects of cultivar and establishment method on pasture production and persistence of tall fescue were evaluated. Tillage prior to planting increased cool‐season grass yield, compared with no‐till overseeding, but the effect on total annual forage production was generally negative. TMQ was the most productive of TF cultivars tested with a mean increase of 53% over K31. Annual ryegrass produced the greatest 3‐year total yield of cool‐season grasses tested. TF cultivars, including summer‐dormant FLE, did not survive beyond a fourth growing season. The total yield over three years of unmodified warm‐season pasture was only surpassed on treatments where IRG was overseeded into existing warm‐season pasture.